Non-Destructive Spectral Systems (NDSS) for modern inspection systems in real-time: challenges and industrial perspectives - Blasco, Jose; Gorla, Giulia; Munera, Sandra; Vitale, Raffaele; Amigo, Jose Manuel (Elsevier, 2025)
The demand for efficient, accurate, and non-invasive inspection methodologies has led to the emergence of Non-Destructive Spectral Systems (NDSS) as transformative tools. NDSS, in combination with chemometrics, enables rapid and precise analyses without damaging the sample, revolutionising traditional inspection approaches and offering accurate quantification and classification, process optimisation, and cost reduction capabilities. This review highlights the principles, advancements, and real-time applications of NDSS in product inspection and quality assurance. Recent technological innovations, data acquisition, computational algorithms, and their applications in the agri-food, pharmaceutical, and environmental monitoring sectors are explored. Furthermore, the challenges associated with their adoption for real-time implementations, including computational demands, calibration complexities, and environmental variability, are discussed. Case studies and emerging research directions provide a comprehensive outlook on the potential of NDSS to address evolving industrial needs. This review underscores the pivotal role of NDSS in enhancing operational efficiency, ensuring product quality, and driving future advancements in analytical instrumentation.